Performance of IMC controllers applied to oil well drilling - Alvarado Silva, Carlos Alexis (2018)
Pressure control during drilling of oil wells can be one of the most complex and dangerous processes at the exploration stage. This study proposes the design and validation of the performance of the Internal Model Controllers (IMC and SIMC) to control the pressure in drilling of oil wells based on the Manage Pressure Drilling (MPD) technique. The MPD adds a control valve in the drilling system to obtain another manipulation variable at the bottom of the well. In the first part of this work, a linear mathematical model of the process was obtained, based on the mechanics of the fluids. The dynamic process presented an integrating element, in addition, it is considered the addition of a time interval between the action of the valve and the response of the variation of the pressure in the bottom of the well. In the second part, the improved IMC driver was designed to compensate the effect of the integrated term with the time delay, looking for the best performance and robustness of the system. Finally, the proposed controller is tested for common problems during drilling simulations (fluid loss, inflows, pipe connection and loss of pump power) showing its viability. In addition, the performance of the closed loop system is compared with a classic PI controller.